Dissimilarities in species assemblages among Amazonian mineral licks. (2nd August 2021) - Griffiths, Brian M.; Cooper, William Justin; Bowler, Mark; Gilmore, Michael P.; Luther, David
Abstract: Mineral lick elevation, size, and distance to the closest human community are all associated with mammal and bird species visitations. The most frequently hunted licks have similar species assemblages. Results indicate high variability in species assemblages at different mineral licks suggesting different species‐specific resource needs at different licks. Abstract in Spanish is available with online material. Abstract : Mineral lick elevation, size, and distance to the closest human community are all associated with mammal and bird species visitations. The most frequently hunted licks have similar species assemblages. Results indicate high variability in species assemblages at different mineral licks suggesting different species‐specific resource needs at different licks. RESUMEN: La elevación, tamaño y la distancia de la collpa a la comunidad humana más cercana están asociados con las visitas de diferentes especies de mamíferos y aves. Las collpas donde se caza con mayor frecuencia tienen conjuntos de especies similares. Los resultados indican una alta variabilidad de conjuntos de especies en diferentes collpas, lo que sugiere que hay diferentes necesidades de recursos específicos por especies en diferentes collpas.